Immunotherapy-Based Therapeutic Strategies for Recurrent Advanced Squamous Cell Carcinoma of the Head and Neck: A Case Report and Literature Review - Nie, Hao; Chen, Ting; He, Kefei; Liang, Chanjin; Guo, Wei; Shi, Xingyuan (Frontiers in Immunology, 2021)
We present a patient with locoregionally advanced laryngeal carcinoma, who experienced recurrence 2 months after surgery. We exploratively treated this patient with immunotherapy combined with targeted therapy with or without radiation therapy. The patient exhibited a significant and durable response. Thus far, there are no standard or effective second-line therapeutic modalities for recurrent locoregionally advanced laryngeal carcinoma. The efficacy of conventional chemotherapy with anti-epidermal growth factor receptor (anti-EGFR) remains unsatisfactory. The addition of immunotherapy resulted in substantial improvement in the progression-free survival (PFS) and overall survival (OS) of this patient. In this case, immunotherapy combined with anti-EFGR was administered, leading to good tumor response; based on this observation, radiotherapy was added to further intensify tumor control. This therapeutic strategy may be a novel option for recurrent locoregionally advanced squamous cell carcinoma of the head and neck.